2021
DOI: 10.3390/met12010032
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and Crystallography Analyses of HSLA Steels with Hardenability Enhanced by Tailored C–Ni Collocation

Abstract: High hardenability is of great importance to ultra-heavy steel plates and can be achieved by tailoring the composition of steel. In this study, the continuous cooling transformation (CCT) curves of two high-strength low-alloy (HSLA) steels (0.16C-0.92Ni steel and 0.12C-1.86Ni steel) were elucidated to reveal the significance of C–Ni collocation on hardenability from the perspective of morphology and crystallography. At a low cooling rate (0.5 °C/s), the 0.12C-1.86Ni steel showed higher microhardness than 0.16C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…The For better comprehension of the relationship between intervariant boundaries and impact toughness, the intervariant boundaries were further categorized into block, subblock and packet boundaries according to the boundary types [13,15], and the densities of the intervariant boundaries were calculated. As shown in Figure 6a, the head exhibits a significantly higher density of block boundaries from different Bain groups than the end, which is a result of its weaker variant selection [8,36]. Previous studies have shown that a lower starting temperature of transformation can be triggered by a higher cooling rate, and thus a greater driving force for phase transformation can be obtained [8,35,37].…”
Section: Discussionmentioning
confidence: 94%
“…The For better comprehension of the relationship between intervariant boundaries and impact toughness, the intervariant boundaries were further categorized into block, subblock and packet boundaries according to the boundary types [13,15], and the densities of the intervariant boundaries were calculated. As shown in Figure 6a, the head exhibits a significantly higher density of block boundaries from different Bain groups than the end, which is a result of its weaker variant selection [8,36]. Previous studies have shown that a lower starting temperature of transformation can be triggered by a higher cooling rate, and thus a greater driving force for phase transformation can be obtained [8,35,37].…”
Section: Discussionmentioning
confidence: 94%